2005
DOI: 10.1063/1.2047555
|View full text |Cite
|
Sign up to set email alerts
|

Structures and energetics of hydrogen-terminated silicon nanowire surfaces

Abstract: The analysis and density-functional tight-binding simulations of possible configurations of silicon nanowires (SiNWs) enclosed by low-index surfaces reveal a number of remarkable features. For wires along <100>, <110>, and <111> directions, many low-index facet configurations and cross sections are possible, making their controlled growth difficult. The 112 wires are the most attractive for research and applications because they have only one configuration of enclosing low-index facets with a rectangular cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 19 publications
4
82
1
Order By: Relevance
“…6,7 Structures and energetics of H-SiNWs were reported by using DFT tight binding method. 8 By passivating the SiNWs surface with H and some halogens including Br, Cl, and I, the electronic structure of wires with diameter ranging from 0.6 to 3 nm has been studied using ab initio DFT calculations. 9 Impurity doped SiNWs have also attracted attention since the dopant atoms provide excess carriers required in device applications, such as diodes and transistors.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Structures and energetics of H-SiNWs were reported by using DFT tight binding method. 8 By passivating the SiNWs surface with H and some halogens including Br, Cl, and I, the electronic structure of wires with diameter ranging from 0.6 to 3 nm has been studied using ab initio DFT calculations. 9 Impurity doped SiNWs have also attracted attention since the dopant atoms provide excess carriers required in device applications, such as diodes and transistors.…”
Section: Introductionmentioning
confidence: 99%
“…These results demonstrate a clear preference for growth along the <110> direction in the smallest Si NWs and along <111> direction in larger ones (Zhong et al, 2007). Cross-sectional HRTEM analysis has revealed that the nanowires could have triangular, rectangular and hexagonal cross section with well -developed facets (Vo et al, 2006) (Jie et al, 2006) (Zhang et al, 2005). The VLS method permits to fabricate the nanowires of well-defined length with diameters as small as 3 nm (Wu et al, 2004).…”
Section: Bottom Up Approachmentioning
confidence: 94%
“…We examined C clusters in 3C-SiC bulk and in hydrogenpassivated SiC NWs grown along the [111] and [100] directions [7,31]. We considered SiC NWs with diameter of about 10Å, constructed from the 3C-SiC structure [5,32].…”
Section: Resultsmentioning
confidence: 99%